2010
DOI: 10.1212/wnl.0b013e3181e042c4
|View full text |Cite
|
Sign up to set email alerts
|

Increased diffusivity in acute multiple sclerosis lesions predicts risk of black hole

Abstract: Objective: Diffusion tensor imaging (DTI) quantifies Brownian motion of water within tissue. Inflammation leads to tissue injury, resulting in increased diffusivity and decreased directionality. We hypothesize that DTI can quantify the damage within acute multiple sclerosis (MS) white matter lesions to predict gadolinium (Gd)-enhancing lesions that will persist 12 months later as T1 hypointensities.Methods: A cohort of 22 individuals underwent 7 brain MRI scans over 15 months. DTI parameters were temporally qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 35 publications
(39 reference statements)
4
63
0
1
Order By: Relevance
“…42,45,[50][51][52] Recent evidence suggests that the size and duration of enhancing lesions, increased radial diffusion on diffusion tensor imaging (DTI), and lower magnetic transfer ratio (MTR) predispose to chronic black holes, matrix destruction, and brain atrophy. 34,45,46,[53][54][55][56][57][58][59][60] Some controversy remains as to the degree of inflammation found in MS cortical lesions as compared with white matter lesions on histologic examination, but these differences are probably related to stage of MS (early vs. chronic disease). [61][62][63] Newer MRI techniques, currently experimental in nature, are giving us a glimpse of what these modalities may tell us in the future about MRI brain pathology and clinical relevance.…”
Section: Background Historical Evolution Of Ms Diagnostic Criteriamentioning
confidence: 99%
“…42,45,[50][51][52] Recent evidence suggests that the size and duration of enhancing lesions, increased radial diffusion on diffusion tensor imaging (DTI), and lower magnetic transfer ratio (MTR) predispose to chronic black holes, matrix destruction, and brain atrophy. 34,45,46,[53][54][55][56][57][58][59][60] Some controversy remains as to the degree of inflammation found in MS cortical lesions as compared with white matter lesions on histologic examination, but these differences are probably related to stage of MS (early vs. chronic disease). [61][62][63] Newer MRI techniques, currently experimental in nature, are giving us a glimpse of what these modalities may tell us in the future about MRI brain pathology and clinical relevance.…”
Section: Background Historical Evolution Of Ms Diagnostic Criteriamentioning
confidence: 99%
“…Although decreased DTI-derived fractional anisotropic (FA) has been demonstrated to reflect myelin damage in multiple sclerosis (MS) (Schmierer et al, 2007), it is not a marker specific to myelin damage since other pathological components may also contribute to diffusion anisotropy change (Werring et al, 1999, Assaf et al, 2002). For example, inflammation associated vasogenic edema has been recognized to increase apparent diffusion coefficient (ADC) and underestimate the DTI-derived FA of fiber tracts (Pasternak et al, 2009, Naismith et al, 2010). Increased cellularity has been demonstrated to decrease DTI-derived ADC (Anderson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…92 In one in vivo study of MS, radial diffusivity appeared to provide the closest correlation with tissue integrity. 93 A multicenter validation study indicated that fractional anisotropy was the most comparable DTI measure across centers and endorsed its use in multicenter clinical trials. 94 Werring et al 95 demonstrated that a steady and moderate increase of the apparent diffusion coefficient can precede the development of new plaques by 6 -8 months, and they indicated that structural changes in prelesion normal-appearing white matter occur before inflammation and BBB leakage.…”
Section: Future Areasmentioning
confidence: 99%